2009
DOI: 10.3354/dao02101
|View full text |Cite
|
Sign up to set email alerts
|

Emerging infectious diseases in cetaceans worldwide and the possible role of environmental stressors

Abstract: We reviewed prominent emerging infectious diseases of cetaceans, examined their potential to impact populations, re-assessed zoonotic risk and evaluated the role of environmental stressors. Cetacean morbilliviruses and papillomaviruses as well as Brucella spp. and Toxoplasma gondii are thought to interfere with population abundance by inducing high mortalities, lowering reproductive success or by synergistically increasing the virulence of other diseases. Severe cases of lobomycosis and lobomycosis-like diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
298
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(312 citation statements)
references
References 126 publications
6
298
0
8
Order By: Relevance
“…As the frequency and severity of stressors increase globally, the relationship between stress and disease in wildlife populations demands greater attention (Lafferty and Kuris 1999;Aguirre and Tabor 2008;Van Bressem et al 2009;Blaustein et al 2012). Infection can influence animal populations via sublethal effects reducing fitness as well as dramatic population-level effects (Scott 1988;Aguirre and Tabor 2008).…”
Section: The Importance Of Increased Attention To Stress and Wildlifementioning
confidence: 99%
“…As the frequency and severity of stressors increase globally, the relationship between stress and disease in wildlife populations demands greater attention (Lafferty and Kuris 1999;Aguirre and Tabor 2008;Van Bressem et al 2009;Blaustein et al 2012). Infection can influence animal populations via sublethal effects reducing fitness as well as dramatic population-level effects (Scott 1988;Aguirre and Tabor 2008).…”
Section: The Importance Of Increased Attention To Stress and Wildlifementioning
confidence: 99%
“…And thus, understanding the intestinal microbiota will aid in managing and maintaining the health of the YFP [9,53]. It has been reported that intestinal flora crucially influenced the nutrient processing, development of the immune system, colonization resistance, and stimulation of the host [32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on T. gondii in marine mammals showed that this parasite is able to reach and infect marine mammals (Cabezón et al, 2011;Rengifo-Herrera et al, 2012). Infection with T. gondii in marine mammals may result in clinical disease (Carlson-Bremer et al, 2015;Mikaelian et al, 2000;Van Bressem et al, 2009). This has been clearly demonstrated in California sea otters (Euhydra lutris nereis) ), Hector's dolphins (Cephalorhynchus hectori) (Roe et al, 2013) and harbour porpoises (Phocoena phocoena) (Herder et al, 2015).…”
Section: Discussionmentioning
confidence: 99%